1979
DOI: 10.1070/pu1979v022n10abeh005616
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoresis in gases

Abstract: The aspirations of manufacturers engaged in rolling bearing research are indicated with emphasis on the resultant need for the use of improved mathematical models. Fundamental mathematical tools are discussed covering the Hertz theory of contacting elastic bodies; rolling bearing fatigue and the Weibull distribution; and load distribution among rolling elements. Finally, some current research problems in the areas of generalized shaft-bearing situations and elastohydrodynamic lubrication are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
(4 reference statements)
2
10
0
Order By: Relevance
“…The concept was first proposed by Deryagin and his coworkers [1][2][3][4] and has been studied experimentally both in ionic 3,5,6 and nonionic solutions. 7,8 In a solution of uncharged solute, for example, small aerosol particles floating in the atmosphere, 9,10 the solute molecules interact with the aerosol particles through the van der Waals and dipole forces. If the interaction between the solute molecules and the particle is attractive, the particle migrates toward the region of higher solute concentration, whereas the movement is toward lower solute concentration if the interacting force is repulsive.…”
Section: Introductionmentioning
confidence: 99%
“…The concept was first proposed by Deryagin and his coworkers [1][2][3][4] and has been studied experimentally both in ionic 3,5,6 and nonionic solutions. 7,8 In a solution of uncharged solute, for example, small aerosol particles floating in the atmosphere, 9,10 the solute molecules interact with the aerosol particles through the van der Waals and dipole forces. If the interaction between the solute molecules and the particle is attractive, the particle migrates toward the region of higher solute concentration, whereas the movement is toward lower solute concentration if the interacting force is repulsive.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that it is sufficient to solve Equation (1) for a flat boundary because the corrections due to finite curvature are of second order of the Knudsen number. In the papers [11][12][13][14], it was shown that the normal component of heat flux and temperature are discontinuous near the boundary of solid. In this case, the boundary conditions have the form (5):…”
Section: Basic Concepts Of Low Knudsen Gas Dynamicsmentioning
confidence: 99%
“…The boundary conditions for thermal conductivity describe the jumps of temperature and the normal component of heat flux. These boundary conditions were discussed in a series of publications [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These forces arise due to the kinetic slip of a fluid flow near the particle in the presence of the temperature gradient along its surface. 3,4 When temperature gradient is caused by an external source then the magnitude of the effect depends upon thermal conductivity of a host medium 1 and of the particle p . In the limiting case when p →ϱ this effect disappears.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of ther-mophoresis was discovered more than one hundred years ago ͑see, e.g., Ref. 4 and references therein͒ the feasibility of the thermophoretic self-action of a heat releasing particle near the interface was not discussed before. The obtained results imply that a heat releasing ͑absorbing͒ particle is attracted ͑repelled͒ to the interface when thermal conductivity of a host medium is less than thermal conductivity of the adjacent medium.…”
Section: Introductionmentioning
confidence: 99%